Ecoinovaç\~ao: Revisitando o conceito - Priscila Koeller; Pedro Miranda; Maria Cecília Junqueira Lustosa; Maria Gabriela Podcameni (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– Innovation with environmental dimension or eco-innovation became a central element in discussions on economic and social development and growing environmental issues arising from human action, as on green economy or green growth debate. With this motivation, this article reviews the relationship between environment, technology and innovation and the conceptual discussion on eco-innovation, focusing on its characteristics and possible changes due to the Oslo Manual, 4th edition. This analysis reinforced some of its fundamental aspects, as the focus to the results achieved on environmental. However, it also reinforced difficulties in measuring eco-innovation (MEI), especially considering life-cycle assessment. At the same time, this paper pointed out that with Oslo Manual, 4th edition, and the possibility of considering other agents besides the companies as eco-innovators could contribute to reduce divergences between analyzed concepts and to consolidate an eco-innovation concept.
Keywords: Q55; 330; eco-innovation; environmental innovation; Oslo Manual